2009
DOI: 10.1016/j.nlm.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A high fructose diet impairs spatial memory in male rats

Abstract: Over the past three decades there has been a substantial increase in the amount of fructose consumed by North Americans. Recent evidence from rodents indicates that hippocampal insulin signaling facilitates memory and excessive fructose consumption produces hippocampal insulin resistance. Based on this evidence, the present study tested the hypothesis that a high fructose diet would impair hippocampal-dependent memory. Adult male Sprague-Dawley rats (postnatal day 61) were fed either a control (0 % fructose) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 69 publications
7
78
1
1
Order By: Relevance
“…It is not wise to administer sugary beverages to dogs for the purposes of increasing persistence on a regular basis, as the chronic consumption of sugars has been linked to long-term neurodegeneration and decreased executive function (van der Borght et al, 2011;Ross et al, 2009). Thus, it would be useful if the results obtained here motivated research on the effects of other nutrients (that similarly activate the vagus nerve) on replenishment.…”
Section: Discussionmentioning
confidence: 99%
“…It is not wise to administer sugary beverages to dogs for the purposes of increasing persistence on a regular basis, as the chronic consumption of sugars has been linked to long-term neurodegeneration and decreased executive function (van der Borght et al, 2011;Ross et al, 2009). Thus, it would be useful if the results obtained here motivated research on the effects of other nutrients (that similarly activate the vagus nerve) on replenishment.…”
Section: Discussionmentioning
confidence: 99%
“…However it is well known that industrial fructose usage causes serious health problems in living organism. It is reported that fructose is taken into the body without being controlled by insulin, which creates dependency, causes cell aging, impairs spatial memory, metabolic syndrome, obesity and many pathologic illness [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…A high fructose (HF) diet causes a number of pathological changes, including oxidative stress, obesity, metabolic syndrome, glucose intolerance, insulin resistance, type II diabetes, liver disease, hypertension and cardiovascular disease (CVD) (2). Unhealthy dietary habits can result in damage to brain health.…”
Section: Introductionmentioning
confidence: 99%